2019
DOI: 10.7567/1347-4065/aaf4b4
|View full text |Cite
|
Sign up to set email alerts
|

Semipolar InGaN blue laser diodes with a low optical loss and a high material gain obtained by suppression of carrier accumulation in the p-waveguide region

Abstract: We obtained InGaN laser diodes (LDs) with a low optical loss (1.9 ± 0.6 cm −1 ) by utilizing an undoped In 0.07 Ga 0.93 N p-waveguide (p-WG) and a remote p-AlGaN electron blocking layer. This improvement, however, was accompanied by a low injection efficiency (37%) and a poor material gain. Electroluminescence measurements and energy band diagram simulations revealed excessive carrier accumulation in the p-WG region, which was suppressed by introducing an undoped indium-free GaN p-WG. This enabled LDs with a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…29 As shown in Figure 7b, a decent value of 2257 cm −1 was extracted, which is comparable to that reported previously for semipolar LDs grown on bulk GaN. 25 Such an unaffected gain coefficient, on the other hand, explains the similar slope efficiencies and power outputs of the LDs on the GaN/sapphire template and the LDs on bulk GaN, even when the threshold current is much higher.…”
Section: G (2 )supporting
confidence: 88%
See 3 more Smart Citations
“…29 As shown in Figure 7b, a decent value of 2257 cm −1 was extracted, which is comparable to that reported previously for semipolar LDs grown on bulk GaN. 25 Such an unaffected gain coefficient, on the other hand, explains the similar slope efficiencies and power outputs of the LDs on the GaN/sapphire template and the LDs on bulk GaN, even when the threshold current is much higher.…”
Section: G (2 )supporting
confidence: 88%
“…Polarization measurements were then carried out by tuning the polarizer so the intensity of the light corresponding to the transverse electric (TE) and transverse magnetic (TM) emission can be obtained. 25 Figure 3c shows the TE and TM emission spectra of the LDs operating at a current of 900 mA. The EL intensity of the TE mode is far stronger than that of the TM mode.…”
Section: T H Imentioning
confidence: 99%
See 2 more Smart Citations
“…As was mentioned previously, one of the drawbacks of using InGaN waveguides, despite technological issues in growing high indium content thick layers [20,21], is higher carrier accumulation [19,22]. MEHARI et al [22] found that in semipolar InGaN LDs, when a part of GaN waveguide is replaced by InGaN layer, carriers accumulate in WG. The carrier concentration in the order of 10 19 cm -3 was found to decrease η i due to unwanted recombination of carriers.…”
Section: Influence Of Ingan Waveguide On Injection Efficiencymentioning
confidence: 96%